Role of Calprotectin as a Biomarker in Periodontal Disease. (21st August 2019) - Wei, Lili; Liu, Mingwen; Xiong, Haofei
Abstract : Periodontal disease (PD) is a common infectious and inflammatory disease characterised by inflammation of tissues surrounding and supporting the teeth and destruction of the associated alveolar bone, eventually resulting in tooth loss. This disease is caused by periodontopathic bacteria in plaque biofilm and resultant innate and adaptive immune responses in periodontal tissues. Calprotectin (CLP) is a calcium-binding protein of the S-100 protein family and is found to be induced by activated granulocytes, monocytes, and epithelial cells. CLP has been shown to play an important role in numerous inflammatory diseases and disorders. Increasing evidence indicates that CLP is involved in the progression of PD, and its levels may be associated with disease severity and outcome of periodontal treatments. This review will summarise recent studies regarding the presence, regulation, and function of CLP in PD. The findings indicate that CLP may be an effective biomarker for diagnosis and treatment for the PD.